Women and leadership in the Jordanian armed forces - Amani Al-Serhan; Raeda Saada; Niveen M. AlSayyed (Administrative Sciences, 2023)
Ever since gaining approval to be admitted to the Jordanian Armed Forces (JAF), Jordanian women have become more visible in this sector. Women were recruited in various fields across the military, including administrative posts, education, and human resources. There is a noticeable gap in the number of women reaching leadership positions despite the quality of their work and their tremendous contributions in this sector. The present study aims to explore the correlation between military culture and environment and women's perceptions of leadership by drawing on quantitative data from female personnel at Al-Hussein Medical Center (HMC). A five-point Likert scale was adopted in the current questionnaire to test the extent of agreement with question items suggested for each aspect of work culture and environment construct. The results demonstrate that women at HMC perceive their work culture and environment positively, which in turn reflects their positive perceptions about their quality of work and their ability to lead. The female participants at HMC demonstrate positive perceptions of gender that challenge prevailing gender norms through gaining necessary support and opportunities for career advancement. The study results imply that supportive work environments have a greater impact on women's aspirations to become leaders.
Keywords: 350; army; gender; Jordanian; leadership; military; performance; women